2010
DOI: 10.1016/j.micron.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Study of environmental biodegradation of LDPE films in soil using optical and scanning electron microscopy

Abstract: An outdoor soil burial test was carried out to evaluate the degradation of commercially available LDPE carrier bags in natural soil for up to 2 years. Biodegradability of low density polyethylene films in soil was monitored using both optical and scanning electron microscopy (SEM). After 7-9 months of soil exposure, microbial colonization was evident on the film surface. Exposed LDPE samples exhibit progressive changes towards degradation after 17-22 months. SEM images reveal signs of degradation such as exfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…Soil-buried LDPE showed active microbial growth on LDPE in 7-9 months, and surface deterioration was confirmed within 17-22 months as determined by SEM analysis (Mumtaz et al 2010). Abrusci et al (2011) tested the biodegradability of photo-degraded polyethylene through Bacillus cereus, B. megaterium, B. subtilis and Brevibacillus borstelensis at 30 and 45 °C.…”
Section: Polyethylenementioning
confidence: 99%
“…Soil-buried LDPE showed active microbial growth on LDPE in 7-9 months, and surface deterioration was confirmed within 17-22 months as determined by SEM analysis (Mumtaz et al 2010). Abrusci et al (2011) tested the biodegradability of photo-degraded polyethylene through Bacillus cereus, B. megaterium, B. subtilis and Brevibacillus borstelensis at 30 and 45 °C.…”
Section: Polyethylenementioning
confidence: 99%
“…Furthermore, Kapanen et al [25] described that the photo-degradation made the surfaces hydrophilic and these surfaces enhanced their affinity to microbes. Similarly, an out door soil burial test was carried out by Mumtaz et al [26,27] to evaluate the degradation of commercially available LDPE carrier bags in soil through the inhabitant microbes. …”
Section: Microscopymentioning
confidence: 99%
“…A large body of evidence has shown that plastics can persist in the environment for hundreds of years often as harmful microscopic particles that are known to be dangerous to the environment, especially for marine ecosystems (Galgani et al 2000;Mumtaz et al 2010). They are also produced from petrochemical sources that may be depleted and take millions of years to be renewed.…”
Section: Introductionmentioning
confidence: 99%